A prospective study of two-dimensional ultrasonography combined with shear wave elastography for pregnancy-related diastasis recti abdominis - Wang, Li; Yun, Ting; Zhang, Dong; Zhong, Jianrong; Yi, Dan; Fu, Wanxi; Li, Molin; Zhang, Yunshan; Wang, Yuexiang (Frontiers in Physiology, 2024)
Objectives: To compare the inter-rectus distance (IRD), rectus abdominis thickness (RAT), and stiffness in women during pregnancy and postpartum and identify the risk and protective factors affecting diastasis recti abdominis (DRA).A total of 171 pregnant women who volunteered to participate in this study were recruited. Using an ultrasonographic diagnostic instrument with shear wave elastography function, IRD, RAT and the Young's modulus of the rectus abdominis muscles were measured at 12 weeks, 37 weeks of pregnancy, and 6 weeks postpartum.The IRD at 37 weeks was significantly higher than that at 12 weeks and then decreased at 6 weeks postpartum, but it was still higher than that at 12 weeks (p < 0.001). RAT and Young's modulus decreased significantly at 37 weeks compared with those at 12 weeks and then recovered at 6 weeks postpartum, but they were lower than those at 12 weeks (p < 0.001). IRD at 12 weeks was significantly higher in multiparae than in primiparae (p < 0.001). Moreover, positive correlation between the RAT and Young's modulus of rectus abdominis muscles at 12 and 37 weeks of gestation and 6 weeks postpartum (p < 0.001) was observed. Multiple linear regression analysis showed that the regression equation was significant (f = 24.856, p < 001).3 Conclusion: Our study identified differences in IRD, thickness and stiffness of the rectus abdominis muscle between early and advanced pregnancy and the postpartum period. The risk and protective factors of DRA may guide pregnant women's protection and treatment.